Predictors of Satisfaction With Life and Health Status of Older People in Brunei: A Gender Comparative Study - Hanif Abdul Rahman; Hanif Abdul Rahman; Hanif Abdul Rahman; Armah Tengah; Armah Tengah; Armah Tengah; Yusnani Mohd Yusof; Ly Slesman; Chang-Yau Hoon; Khadizah H. Abdul-Mumin; Khadizah H. Abdul-Mumin; Khadizah H. Abdul-Mumin (Frontiers Media S.A., 2022)
Objective: To investigate predictors of life satisfaction and healthy aging with focus on gender differences among older people in Brunei Darussalam.Methods: A cross-sectional study on older people recruited by proportionate sampling. Multiple linear regression stratified by gender was applied.Results: 45.6% of life satisfaction of older women were strongly associated with self-perceived health, social relationship, and education level. For older men, 26.3% of the variance of life satisfaction was predicted by physical functioning or disability, and social relationship. For older women, 38.9% of the variance of health status can be explained with satisfaction with life, and difficulty to do daily tasks. For older men, 33.1% of the variance of health status can be accounted by income, number of children, presence of chronic illness, and diabetes.Conclusion: This paper discusses the unique gender differences of older people from a global perspective. Policymakers and stakeholders need to account for local and contextual differences before adopting international guideline. Particularly, on the maintenance or further promotion social interactions, active engaging elderly in health maintenance, and physical and mental functioning of the older population.